PROJECT PERFORMANCE ANALYSIS USING BALANCED SCORECARD (CASE STUDY: MANAGE SERVICE PROJECT AT PT. X) - Christian, Yonathan; Sugeng Suroso; Dhian Tyas Untari (Dinasti International Journal of Management Science, 2022)
The research aims to measure the performance of manage service project at PT.X which is run at one of the state-owned banks in Indonesia with a balanced scorecard approach. It was conducted by measuring the level of project performance against the four performance perspectives in the balanced scorecard, namely the customer perspective, financial perspective, internal business process perspective, and learning and development perspective. The research is a qualitative descriptive research. The primary data are the results of interviews and observations, and the results of a survey conducted by PT.X project management which are used to measure the performance of the customer perspective and the learning and development perspective and the internal business process perspective. While the measurement of financial performance using data from interviews and observations and data processing. Informants at the research were project workers from the project director level to the team leader. Research results show that the overall performance of PT.X's managed service projects is in good condition but still cannot reach the SLA achievement target and project billing of 100%. On the customer's perspective shows the performance of "Good". The measurement results from a financial perspective show a "Good" performance where the project's financial performance shows that it is quite economical and efficient but not yet effective. The results of measurement and analysis of performance from the perspective of internal business processes show “good” performance with a note that the number of technicians is needed and the provision of backup devices is needed. The results of the measurement and analysis of performance from a learning and development perspective show a "good" performance with a note the need for OSH training for field workers and leadership for team leaders. Finally, the research prove that the balanced scorecard can be used in analyzing project performance and is able to provide strategic proposals with 4 perspectives.